GENERATION Z’S PERCEPTION OF FLEXIBLE WORK CULTURE AND ITS IMPACT ON PRODUCTIVITY - Abdul Fidayan; Mutia Tri Satya (Multifinance, 2025)
The rapid transformation of work systems driven by digitalization and the post-pandemic era has introduced flexible work culture as a new norm, particularly affecting Generation Z employees. This study aims to analyze the perception of Generation Z toward flexible work culture and its impact on individual productivity. A quantitative research approach was used with a total of 271 respondents consisting of Generation Z employees from various business sectors in Indonesia. Data were collected using a Likert-scale questionnaire adapted from validated instruments on work flexibility and productivity, and analyzed using SPSS 27 through validity, reliability, correlation, and simple linear regression tests. The results show a strong and significant positive relationship between the perception of flexible work culture and individual productivity (R = 0.726; R² = 0.527; Sig. < 0.05). This means that 52.7% of productivity variation can be explained by employees’ perception of flexibility in work time, location, and organizational support. However, role ambiguity and distractions in hybrid settings remain key challenges that hinder optimal performance. The study concludes that a positive perception of flexible work culture significantly enhances productivity when supported by clear role definitions, open communication, and trust-based leadership. Future research is suggested to include variables such as motivation, digital leadership, and work-life balance to better understand the behavioral dynamics of Generation Z in modern workplaces.